2004
DOI: 10.1097/01.asn.0000146121.72699.86
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Glomerular Lesions Involves Coordinated Restructuring of Glomerular Microvasculature

Abstract: Abstract. There is increasing evidence from both human and experimental studies that at least partial reversal of glomerulosclerosis can be achieved by glomerular remodeling. This requires substantial changes in glomerular architecture, specifically of glomerular capillaries. It was the purpose of the present study to characterize the stereologic and topologic characteristics of glomerular capillaries when partial reversal of glomerular lesions is achieved by high-dose angiotensinconverting enzyme inhibitor tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 29 publications
3
67
0
Order By: Relevance
“…44 This remodeling of glomerular architecture suggests some form of regeneration of the capillary network. 45,46 Actually, three-dimensional reconstruction studies of the glomerular tuft showed that RAS inhibitor therapy enlarged the volume of intact capillaries by up 40%-structural changes that allowed the kidney to regain function with time. 47 Glomerular remodeling also was observed in 10 patients with type 1 diabetes after 10 yr of normoglycemia induced by pancreatic transplantation.…”
Section: Regression and Remission Of Nondiabetic Ckdmentioning
confidence: 99%
“…44 This remodeling of glomerular architecture suggests some form of regeneration of the capillary network. 45,46 Actually, three-dimensional reconstruction studies of the glomerular tuft showed that RAS inhibitor therapy enlarged the volume of intact capillaries by up 40%-structural changes that allowed the kidney to regain function with time. 47 Glomerular remodeling also was observed in 10 patients with type 1 diabetes after 10 yr of normoglycemia induced by pancreatic transplantation.…”
Section: Regression and Remission Of Nondiabetic Ckdmentioning
confidence: 99%
“…Regression was associated with a decrease in mean glomerular volume, a decreased number of capillary segments per glomerulus, and a decreased total length of capillaries per glomerulus but without any significant change in the length of individual capillary segments and no change of numerical capillary density of the tuft. 10 We then chose to expand on these previous approaches by studying branching patterns of glomerular topology by confocal analysis coupled with a novel graph theory analysis of the morphological complexity of the glomerulus in progressive disease versus regression states. Limitations of this approach include the technical limits on depth of glomeruli that can be adequately visualized and thus analyzed by this method.…”
Section: Discussionmentioning
confidence: 99%
“…New glomeruli cannot be generated after term birth in humans, but segmentally scarred glomeruli could potentially undergo regression of existing sclerosis by resorption of areas with matrix accumulation and enhanced growth of the remaining capillary loops. 10,12 Our previous data have shown that such ARBinduced improvement in sclerosis was indeed linked to less matrix accumulation in glomeruli, with an associated decrease in plasminogen activator inhibitor-1 (PAI-1) and increased plasmin activity. 4 PAI-1 is the major inhibitor of the plasmin/plasminogen activator system and inhibits both fibrinolysis and proteolysis.…”
mentioning
confidence: 99%
“…We initially used coefficients of kidney density (1.04 g/cm 3 ) and shrinkage (1.08) established and commonly used for adult rats 14 . However, these coefficients yielded much higher number of glomeruli than those measured by the fractionator/dissector method at all time points measured.…”
Section: Kidney Density Shrinkage Coefficient and Glomerular Size DImentioning
confidence: 99%